An introduction to engine testing and development - Atkins, Richard D., 1940- (Society of Automotive Engineers, 2009)
With useful information for graduate students, new test technicians, and established engineers, this book explains the test process - from setting up a dynamometer test facility to testing for performance and durability. Combustion analysis and emissions, and new test trends are also covered.
Title from PDF title page (SAE Web site, 08/15/2012).
"SAE Order no. R-344"--T.p. verso.
Includes index.
Keywords: Automobiles -- Motors -- Testing.; Automobiles -- Motors -- Design and construction.; elektronické knihy; electronic books